PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, DAN DEWAN KOMISARIS INDEPENDEN TERHADAP PENGUNGKAPAN SUSTAINABILITY REPORT : Studi Empiris pada Perusahaan BUMN yang Terdaftar di Bursa Efek Indonesia - Pakpahan, Dian Lamsihar; Darlis, Edfan; Hanif, Rheny Afriana (LPPM Universitas Bina Bangsa, 2025)
This study aims to analyze the Influence of Profitability, Company Size, and Independent Board of Commissioners on Sustainability Report Disclosure (Empirical Study on State-Owned Enterprises Listed on the Indonesia Stock Exchange in 2020-2022). The data used in this study are secondary data. The sample was selected using the purposive sampling method on the annual report and sustainability report. The number of companies sampled in this study was 14 companies with 3 years of observation, so that the total sample obtained was 42 company data. The data analysis technique used was descriptive statistical analysis and multiple linear regression with the SPSS 25 software program. The results of the study concluded that profitability had an effect on sustainability report disclosure. Meanwhile, company size and independent board of commissioners do not affect sustainability report disclosure